Task allocation-based modified bacterial foraging algorithm for maximising reliability of a heterogeneous distributed system. (29th May 2019) - Abbache, Farid; Kalla, Hamoudi
Modified bacterial foraging algorithm for allocation and scheduling tasks on processors and links with high reliability is proposed (MBFA). MBFA ensure high reliability without redundancy of processors or links by using an efficient and simple structure. MBFA is improved by adding an efficient model to deal with the weak solution (i.e., allocation with low reliability). Also a simulated annealing technique is integrated into MBFA in order to strengthen the search of best solution. The efficiency and effectiveness of MBFA are tested using random generated problems. MBFA is tested over the published approaches HPSO and GAA using density parameter ( DS ), number of nodes ( N ) and the communication to computation ratio parameter ( CCR ). The results show the superiority of MBFA over the published approaches in all test cases.